Case files. - Toy, Eugene C. (McGraw-Hill Medical, 2013)
Sixty high-yield pediatrics cases help you sharpen your diagnostic and problem-solving skills. You need exposure to high-yield cases to excel on the pediatrics clerkship and the shelf-exam. Case Files: Pediatrics presents sixty real-life cases that illustrate essential concepts. Each case includes complete discussion, clinical pearls, references, definitions of key terms, and USMLE-style review questions with detailed explanations of the correct answers. With this system, you'll learn in the context of real patients, rather than merely memorize facts.